Difference between revisions of "Mock AIME 6 2006-2007 Problems/Problem 10"
(→Solution) |
|||
(38 intermediate revisions by the same user not shown) | |||
Line 3: | Line 3: | ||
==Solution== | ==Solution== | ||
− | Let <math>R</math> be the rotational matrix for a point | + | Let <math>R(\theta)</math> be the rotational matrix for a point to rotate <math>(\theta)</math> around the origin: |
− | <math>R=\begin{ | + | <math>R(\theta)=\begin{bmatrix} cos(\theta) & -sin(\theta)\\ sin(\theta) & cos(\theta) \end{bmatrix}</math> |
For <math>\theta = 90^\circ</math> | For <math>\theta = 90^\circ</math> | ||
− | <math>R=\begin{ | + | <math>R=\begin{bmatrix} cos(90^\circ) & -sin(90^\circ)\\ sin(90^\circ) & cos(90^\circ) \end{bmatrix}=\begin{bmatrix} 0 & -1\\ 1 & 0 \end{bmatrix}</math> |
− | Let <math>P_r</math> be the point of rotation | + | Let <math>P_r</math> be the point of rotation, then <math>P_r=\begin{bmatrix} 2000-n \\ n \end{bmatrix}</math> |
− | <math> | + | Let's write <math>P_n</math> in matrix form as: <math>P_n=\begin{bmatrix} P_{x_n} \\ P_{y_n} \end{bmatrix}</math>, where <math>P_{x_n}</math> and <math>P_{y_n}</math> are the <math>x</math> and <math>y</math> coordinates of <math>P_n</math> respectively. |
− | <math>P_{n+1} | + | We can write the equation of <math>P_{n+1}</math> by translating the <math>P_n</math> to the origin, multiply it by the rotation matrix <math>R</math> and then add the point subtracted: |
+ | <math>P_{n+1}=(R)(P_n-P_r)+P_r=\begin{bmatrix} 0 & -1\\ 1 & 0 \end{bmatrix}\begin{bmatrix} P_{x_n}-(2000-n) \\ P_{y_n}-n \end{bmatrix}+\begin{bmatrix} 2000-n \\ n \end{bmatrix}=\begin{bmatrix} 2000-P_{y_n} \\ P_{x_n}+2n-2000 \end{bmatrix}</math> | ||
+ | |||
+ | Now we find <math>P_{n+2}</math>: | ||
+ | |||
+ | <math>P_{n+2}=\begin{bmatrix} 2000-P_{y_{n+1}} \\ P_{x_{n+1}}+2n-2000 \end{bmatrix}=\begin{bmatrix} 2000-(P_{x_n}+2n-2000) \\ (2000-P_{y_n})+2(n+1)-2000 \end{bmatrix}=\begin{bmatrix} 4000-P_{x_n}-2n \\ -P_{y_n}+2(n+1) \end{bmatrix}</math> | ||
+ | |||
+ | For this problem, we're only interested in the <math>y</math>-coordinate. So, | ||
+ | |||
+ | <math>P_{y_{n+1}}=P_{x_n}+2n-2000</math> | ||
+ | |||
+ | <math>P_{y_{n+2}}=-P_{y_n}+2(n+1)</math> | ||
+ | |||
+ | Notice that since <math>2(n+1) \equiv 0\; (mod\;2)</math>, then <math>P_{y_{n+2}} \equiv P_{y_n}\; (mod\;2)</math>. | ||
+ | |||
+ | Since <math>P_{y_0}=0</math> and we're looking at a <math>y</math>-coordinate of <math>433</math>, we notice that <math>433 \equiv 1\; (mod\;2) \not\equiv P_{y_0}\; (mod\;2)</math>. | ||
+ | |||
+ | Therefore we need to calculate <math>P_{y_1}</math>: | ||
+ | |||
+ | <math>P_{y_1}=P_{x_0}+(2)(0)-2000=2007-2000=7</math> | ||
+ | |||
+ | <math>P_{y_m} \equiv 1\; (mod\;2)\equiv P_{y_1}\; (mod\;2)</math> | ||
+ | |||
+ | So, we use the recursive formula for <math>P_{y_{n+2}}</math> starting with <math>P_{y_1}</math>: | ||
+ | |||
+ | <math>P_{y_3}=-P_{y_1}+(2)(1)+2</math> | ||
+ | |||
+ | <math>P_{y_5}=-P_{y_3}+(2)(3)+2</math> | ||
+ | |||
+ | <math>P_{y_7}=-P_{y_5}+(2)(5)+2</math> | ||
+ | |||
+ | and we can find <math>P_{y_{2q+1}}</math> for <math>q \in \mathbb{Z}^{+}</math> as: | ||
+ | |||
+ | <math>P_{y_{2q+1}}=-P_{y_{2q-1}}+2(2q-1)+2=-P_{y_{2q-1}}+4q</math> | ||
+ | |||
+ | <math>P_{y_{2q+1}}=(-1)^q P_{y_1}+4(q-(q-1)+(q-2)-(q-3)+....+0)</math> | ||
+ | |||
+ | <math>P_{y_{2q+1}}=(-1)^q P_{y_1}+4 \left( \begin{cases} q, & q\;is\;odd \\ 0, & q\;is\;even\end{cases}+\begin{cases} -\frac{q-1}{2}, & q\;is\;odd \\ \frac{q}{2}, & q\;is\;even\end{cases} \right) </math> | ||
+ | |||
+ | <math>P_{y_{2q+1}}=(-1)^q P_{y_1}+ \begin{cases} 2q+2, & k\;is\;odd \\ 2q, & q\;is\;even\end{cases}=(-1)^q P_{y_1}+ 2q+\begin{cases} 2, & q\;is\;odd \\ 0, & q\;is\;even\end{cases}</math> | ||
+ | |||
+ | <math>P_{y_{2q+1}}=(-1)^qP_{y_1}+2q+(1-(-1)^q)=(-1)^q(P_{y_1}-1)+2q+1</math> | ||
+ | |||
+ | Since <math>P_{y_{2q+1}}=433</math>, and <math>P_{y_1}=7</math> then we solve for <math>q</math> as follows: | ||
+ | |||
+ | <math>(-1)^q(7-1)+2q+1=433</math> | ||
+ | |||
+ | <math>q=\frac{433-1-(-1)^q6}{2}=216-(-1)^q3</math> | ||
+ | |||
+ | Since <math>\pm 1 \equiv 1\; (mod\;2)</math> then <math>\pm 3 \equiv 1\; (mod\;2)</math> and <math>(-1)^q3 \equiv 1\; (mod\;2)</math> | ||
+ | |||
+ | Therefore <math>(216-(-1)^q3) \equiv 1\; (mod\;2)</math> and <math>q</math> is odd. | ||
+ | |||
+ | So, <math>q=216-(-1)(3)=219</math> and <math>m=2q+1=(2)(219)+1=\boxed{439}</math> | ||
~Tomas Diaz. orders@tomasdiaz.com | ~Tomas Diaz. orders@tomasdiaz.com | ||
+ | |||
+ | {{alternate solutions}} |
Latest revision as of 15:20, 25 November 2023
Problem
Given a point in the coordinate plane, let
be the
rotation of
around the point
. Let
be the point
and
for all integers
. If
has a
-coordinate of
, what is
?
Solution
Let be the rotational matrix for a point to rotate
around the origin:
For
Let be the point of rotation, then
Let's write in matrix form as:
, where
and
are the
and
coordinates of
respectively.
We can write the equation of by translating the
to the origin, multiply it by the rotation matrix
and then add the point subtracted:
Now we find :
For this problem, we're only interested in the -coordinate. So,
Notice that since , then
.
Since and we're looking at a
-coordinate of
, we notice that
.
Therefore we need to calculate :
So, we use the recursive formula for starting with
:
and we can find for
as:
Since , and
then we solve for
as follows:
Since then
and
Therefore and
is odd.
So, and
~Tomas Diaz. orders@tomasdiaz.com
Alternate solutions are always welcome. If you have a different, elegant solution to this problem, please add it to this page.